How to Realize E-learning Efficiently in Higher Education during COVID-19 Epidemic: Practices in 2020~2022 - Yao, Shun; Li, Defu; Yohannes , Alula; Song, Hang; Li, Jiying (Current Overview on Science and Technology Research Vol. 8, 2022)
During the three years of COVID-19 epidemic (2020~2022), the face-to-face classroom scene transforms to a network virtual space from time to time, and the construction of distance education and resource sharing platform becomes more and more important. In order to provide practical examples and referential strategies for the efficient use of various resources to achieve mixed teaching in the post epidemic era, the following paper comprehensively introduces the social needs, framework composition, main functions and expected objectives of the system, analyzes the existing main problems and development bottlenecks in combination with the teaching practices, and shares the experience of distance teaching through the actual applications. Currently, the two-level (college and university) public platforms shared by teachers and students were recognised as a possible resource for pertinent research and platform development. Finally, a few "pocket experiments" were successfully conducted at students' homes with the help of teachers who were guiding them remotely. Information and communication technologies are anticipated to play an increasingly important role in the future during the epidemic or other crises involving global public health.